Fiscal sustainability indicators and policy design in the face of ageing - Geert Langenus (National Bank of Belgium, 2006)
Mainly due to increasing concerns about the potential impact of population ageing the sustainability of public finances has become one of the key issues in fiscal assessments. This paper briefly reviews the different theoretical benchmarks and empirical tests for sustainability and assesses the sustainability of public finances in euro area countries on the basis of the latest projections of the Ageing Working Group of the EU Economic Policy Committee. Two alternative operational indicators for fiscal sustainability are proposed and appropriate policy options to restore fiscal sustainability are explored for three individual euro area countries. Pre-funding strategies that create the budgetary room that is needed to finance ageing costs in advance require important consolidation efforts for most euro area countries and can imply aiming at significant budgetary surpluses in the coming years for some. However, a simplified technical exercise assessing the evolution of the fiscal burden of the average worker shows that such strategies generally imply a more even distribution of the fiscal burden across generations than more gradual adjustment strategies.
Keywords: H55; H60; 330; population ageing; fiscal sustainability; medium-term objectives for fiscal policy; Alternde Bevölkerung; Öffentliche Finanzen; Bevölkerungsprognose; Bevölkerungsentwicklung; EU-Staaten